INDONESIA SHARI'AH COMPLIANCE STOCK RETURN BEHAVIOUR - Helma Malini; Mohamad Jais; Rossazana Ab Rahim (Jurnal Manajemen Indonesia, 2015)
This study aims to measures the behaviour of Indonesia Shari'ah compliance stock return. The measurement of return behaviour toward volatility will proved the capability of Indonesia Shari'ah compliance toward volatility that happened in Indonesia during the period of observation. Investing in Shari'ah compliance is quite different than investing in conventional stock which followed the capital market set of rules and law, Shari'ah compliance follows not only the capital market set of laws and but also the Islamic principles of principles. Most of the previous studies examine issues related to the conventional stocks and market. The present study take one step further by investigating issue related to Shari'ah compliance instrument. In the case of Shari'ah stock price in Indonesia, the dynamics volatility of the stock price can be minimized by taking an integrated screening process to the listed company, as precautions steps toward volatility